Case Report: Anti-platelet factor 4 -mediated immunothrombosis in a patient with ANCA vasculitis – a shared mechanism of NETosis - Remez-Gabay, Lital; Vdovich, Olga; Akria, Luiza; Kruzel-Davila, Etty (Frontiers in Immunology, 2025)
Anti-platelet factor 4 (PF4) immunothrombosis is characterized by thrombocytopenia, thrombosis and enhanced NETosis and has been described in the absence of prior heparin exposure. This case report describes a patient with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) who, while under immunosuppression, developed anti-PF4-mediated immunothrombosis, with NETosis significantly elevated compared to baseline markers observed during AAV. Treatment with intravenous immunoglobulin (IVIG) led to resolution of the syndrome, marked by a reduction in NETosis markers, restoration of platelet counts, and alleviation of the hypercoagulable state. We review the epidemiology, pathogenesis, clinical manifestations, and management strategies of thrombotic anti-PF4 immune disorders, highlighting the roles of AAV and dysregulated NETosis as key triggers. Early recognition of anti-PF4-mediated immunothrombosis without prior heparin exposure is critical, as prompt treatment with IVIG and direct thrombin inhibitors can significantly improve outcomes. This case underscores the interplay between NETosis, ANCA vasculitis, and thrombotic anti-PF4 immune disorders, emphasizing the therapeutic potential of IVIG in mitigating NETosis-related complications.